2015
DOI: 10.1007/s00467-015-3129-z
|View full text |Cite
|
Sign up to set email alerts
|

Impact of gestational age, sex, and postnatal age on urine biomarkers in premature neonates

Abstract: Background Urine proteins may help understand physiology and diagnose disease in premature infants. Understanding how urine proteins vary by degree of prematurity, sex and postnatal day is warranted. Methods We performed a prospective cohort study to assess the independent correlation of 14 urine biomarkers (measured on postnatal days 1–4) with gestational age (GA), sex, and postnatal age in 81 premature infants (mean 1017 grams) without acute kidney injury using random effects mixed model. Results Neutrop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
51
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(55 citation statements)
references
References 21 publications
(21 reference statements)
2
51
1
1
Order By: Relevance
“…We could not assess the impact of postnatal age on urinary biomarkers. Saeidi et al (22) showed that postnatal age affects urine biomarkers measured in the first 4 d of life in preterm infants without AKI. The nested casecontrol study design was not intended to assess the incidence of AKI; it has the advantage of cost and effort reduction with relatively minor loss in statistical efficiency compared with the full-cohort approach (23).…”
Section: Discussionmentioning
confidence: 99%
“…We could not assess the impact of postnatal age on urinary biomarkers. Saeidi et al (22) showed that postnatal age affects urine biomarkers measured in the first 4 d of life in preterm infants without AKI. The nested casecontrol study design was not intended to assess the incidence of AKI; it has the advantage of cost and effort reduction with relatively minor loss in statistical efficiency compared with the full-cohort approach (23).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, acute changes in fluid status, which occur during this time period, may have an important effect on SCr values (4,5). Fortunately, urine protein biomarkers show promise of someday being able to help diagnose AKI early in the disease process by noninvasively measuring specific urine proteins (6). Improving the ability to reliably detect AKI would have important implications in the ability to care for critically ill neonates and will also improve the ability to perform clinical research.…”
Section: Introductionmentioning
confidence: 99%
“…Prior literature has shown that in premature infants without AKI, urine proteins will be highest among those with the lowest GA, probably because of the passive loss of proteins in the context of immature tubular function (6)(7)(8). Previously, we (7) and others (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18) have published data on the ability of urine biomarkers to predict AKI in neonates; however, these studies are limited by the size of the cohort or the use of nested case-control methods, with most of these studies evaluating only one biomarker.…”
Section: Introductionmentioning
confidence: 99%
“…Urinary biomarkers demonstrated a significant change 24 h prior to contemporary creatinine-based neonatal AKI definition [28]. It is particularly important to recognize the differences in omics biomarkers across different gestational ages, postnatal days, and fluid balance status when designing future validation studies [29][30][31][32].…”
Section: Drug-induced Nephrotoxicitymentioning
confidence: 99%